2001
DOI: 10.1136/jech.55.9.648
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of alcoholic beverages and subjective health in Spain

Abstract: Study objective-To examine the relation between alcohol and main alcoholic beverage consumption and subjective health in Spain. Design-Logistic regression analysis using a cross sectional survey based on self reported data on alcohol and alcoholic beverage consumption, subjective health and the principal confounding factors (age, sex, civil status, educational level, job status, social support, region of residence, size of town or city, tobacco consumption, physical activity during leisure time and work hours,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 22 publications
3
24
1
Order By: Relevance
“…Other studies from around the world have found moderate alcohol consumption to be positively related to general health status [30][31][32][33][34][35] and heavy drinking or 'intoxication' negatively related [30][31][32]35 . Our definition of heavy drinking (2+ drinks per day for men, 1+ drink per day for women) would be considered low to moderate alcohol intake in other studies [32][33][34][35] which is likely related to the cultural perceptions regarding alcohol in different countries. The relationship between alcohol intake and general health may also vary by gender 31,[34][35] and the type of alcohol ingested (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies from around the world have found moderate alcohol consumption to be positively related to general health status [30][31][32][33][34][35] and heavy drinking or 'intoxication' negatively related [30][31][32]35 . Our definition of heavy drinking (2+ drinks per day for men, 1+ drink per day for women) would be considered low to moderate alcohol intake in other studies [32][33][34][35] which is likely related to the cultural perceptions regarding alcohol in different countries. The relationship between alcohol intake and general health may also vary by gender 31,[34][35] and the type of alcohol ingested (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between alcohol intake and general health may also vary by gender 31,[34][35] and the type of alcohol ingested (e.g. wine, beer, hard liquor) [32][33]35 . We found no differences by gender [data not shown], however, we cannot assess the independent effect of different types of alcohol due to the question format used in the BRFSS.…”
Section: Discussionmentioning
confidence: 99%
“…In Scandinavian and Anglo-Saxon countries a ''J-shaped'' relationship has been described, with suboptimal health being more frequent in abstainers and excessive drinkers than in moderate drinkers (Gronbaek et al, 1999;Poikolainen and Vartiainen, 1999;Poikolainen et al, 1996;San Jose´et al, 1999;Theobald et al, 2003;Van Dijk et al, 2004). Yet, the only study conducted in Mediterranean countries observed an inverse relationship, whereby the frequency of suboptimal health declined with alcohol consumption, to the extent that even excessive drinkers reported better health than did nondrinkers (Guallar-Castillo´n et al, 2001).…”
mentioning
confidence: 95%
“…After adjustment for sociodemographic characteristics, lifestyle and chronic disease, moderate drinkers report better health than nondrinkers in most studies, including those that distinguish between former and never drinkers (Gronbaek et al, 1999;Guallar-Castillo´n et al, 2001;Poikolainen and Vartiainen, 1999;Poikolainen et al, 1996;San Jose´et al, 1999;Theobald et al, 2003;Van Dijk et al, 2004).…”
mentioning
confidence: 97%
“…Wine is the most common type of alcoholic beverage in Spain as it accounts for more than 50% of daily alcohol intake (Rodríguez-Artalejo et al, 1999;Guallar-Castillon et al, 2001;Sieri et al, 2002;Schroder et al, 2005).…”
Section: Introductionmentioning
confidence: 99%